(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the implementation of Content and Language Integrated Learning (CLIL) as an approach to teaching English to secondary school students. It examines the theoretical foundations, practical methods, and outcomes of CLIL, drawing on recent literature and empirical data. The study highlights the benefits and challenges of CLIL, offering practical suggestions for educators to enhance language acquisition while delivering subject content.